Eco-friendly anticorrosive epoxy coating from Ixora leaf extract: A promising solution for steel protection in marine environment. (15th March 2022) - Veedu, Krishnapriya Karattu; Mohan, Sangeetha; Somappa, Sasidhar Balappa; Gopalan, Nishanth Karimbintherikkal
Abstract: Emerging apprehensions about environmentally benign anticorrosive materials, biomaterials received a great attention in the area of protective coatings. Here in we investigated the anticorrosive performance of easily available Ixora finlaysoniana leaf extract and its applicability in epoxy coatings on steel in marine environment. Noticeable corrosion inhibition of crude extract from electrochemical analysis prompted the isolation of most active inhibitor compound among the constituent phytochemicals. Structural elucidation efforts on the isolated compound have substantiated the –OH and –OCH3 functional groups alongside aromaticity. Formation of an insoluble organometallic inhibitive barrier by the interaction of Fe and phytochemicals at metal-electrolyte interface provided the promising inhibition efficiency and stability towards metal dissolution. Exploiting the corrosion inhibition property, a durable, environmentally benign extract-based hybrid epoxy coating was developed for steel protection in 3.5 wt% NaCl. The novel anticorrosive organic-inorganic hybrid coating offered exceptional corrosion resistance than hybrid materials reported till now. Furthermore, while comparing the anticorrosive property of commercially available toxic anticorrosive pigments with the corrosion resistance of prepared non-toxic hybrid, it is impossible to tell apart. Continuous electrochemical study over the period of fifty days ensured durability of the coating which reflected the successful integration of eco-friendly passive inorganic and active organic inhibitive component on steel in saline media. In broad spectrum, the completely eco-friendly anticorrosive coating developed in this work contributes a sustainable development of biomaterial-based corrosion prevention. Graphical abstract: Image 1 Highlights: Anticorrosive property of Ixora leaf extract is utilized for steel protection. Active inhibitor in crude extract isolated and identified its functional groups. Resolved compatibility issues of extract in epoxy via an organic-inorganic hybrid. Non-toxic 'green' hybrid equipotential with commercial toxic anticorrosive inorganic pigments. Fabricated eco-friendly, durable and efficient anticorrosive epoxy coating.